1986
DOI: 10.1111/j.1532-950x.1986.tb00165.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal Mucoceles in Dogs

Abstract: Eight cases of pharyngeal mucoceles were diagnosed in 49 dogs with salivary mucoceles over a 7 year period. Five of the eight pharyngeal mucoceles were seen in Miniature Poodles. The presenting complaint in all eight dogs was labored breathing, with or without coughing upon excitement or exercise. Diagnosis was made by aspirating a thick mucoid fluid from the pharyngeal swelling. Treatment consisted of resection of the mandibular and sublingual salivary glands on the affected side and aspiration of the mucocel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…Neoplasia, sialoliths, trauma and glandular foreign bodies have been reported as causes of mucocoeles in dogs (Trumpatori and others 2007). Mucocoeles most frequently affect the sublingual salivary gland (Spreull and Head 1967, Weber and others 1986, Smith 2005), but mucocoeles affecting the parotid and zygomatic gland have been reported (Schmidt and Betts 1978, Bellenger and Simpson 1992). The zygomatic salivary gland is a globular or pyramidal structure that lies in the rostral orbit lateral to the part of the maxilla that contains the roots of the upper molar teeth.…”
Section: Figurementioning
confidence: 99%
“…Neoplasia, sialoliths, trauma and glandular foreign bodies have been reported as causes of mucocoeles in dogs (Trumpatori and others 2007). Mucocoeles most frequently affect the sublingual salivary gland (Spreull and Head 1967, Weber and others 1986, Smith 2005), but mucocoeles affecting the parotid and zygomatic gland have been reported (Schmidt and Betts 1978, Bellenger and Simpson 1992). The zygomatic salivary gland is a globular or pyramidal structure that lies in the rostral orbit lateral to the part of the maxilla that contains the roots of the upper molar teeth.…”
Section: Figurementioning
confidence: 99%
“…The secretory pathway of the salivary glands extends from the microscopic alveoli, intercalated ducts, intralobular ducts, interlobular ducts, and lobular ducts to the visible lobar and excretory ducts . Disruption of this secretory pathway (mostly in the sublingual gland) results in accumulation of saliva in the deeper structures of the intermandibular space, the angle of the jaw or the upper salivary region . The causes of salivary mucocele are poorly understood, although blunt trauma, foreign bodies, and sialoliths have been proposed…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that cervical mucocele is the most common form of this condition [9]. Previous studies have also pointed out that resection of the mandibular and sublingual salivary glands alongside drainage and excision of the redundant tissues is the most definitive treatment of this condition [9,10] although in a high percentage of cases (42%) drainage alone was employed for treatment of the affected animals which resulted in the recurrence of the condition within the next 48 hours [9]. This scenario was also observed in the present case, and, as stated by the dog's owner, the only form of treatment the animal had received before surgery consisted of drainage and injection of povidone iodine solution as a cauterizing agent which had merely complicated the situation.…”
Section: Discussionmentioning
confidence: 99%